Pemanfaatan Grup Whatsapp Oleh Petani Hidroponik Soloraya (Kohisora) Sebagai Media Informasi Pertanian - Umi Hanifah; Suminah Suminah; Putri Permatasari (Jurnal Sosial Ekonomi Pertanian, 2023)
The use of WhatsApp group feature is used by hydroponic farmers as a medium of information and discussion and encourages farmers to follow the development of agricultural information actively. The existence of WhatsApp groups has an impact on farmers in the form of behavior changes that are reviewed by cognitive, affective, and psychomotor components. This study aims to determine the behavior of hydroponic farmers in using WhatsApp groups, analyze supporting factors for changes in hydroponic farmer behavior consisting of digital literacy and intensity of media use and analyze the influence of digital literacy and intensity of media use on hydroponic farmer behavior. This study used a descriptive quantitative approach and sampling techniques using simple random sampling. The sample used was 67 members of the Soloraya Hydroponic Community WhatsApp group, and the analysis method used multiple linear regression. The results showed that the behavior of hydroponic community members which includes cognitive, affective, and psychomotor components was in the high category of 55%. Supporting factors in the form of digital literacy are in the high category, while the intensity of social media use is in the low category. Digital literacy and the intensity of social media use together have a positive and significant influence on the behavior of members of the Hydroponics Community. Partially, digital literacy has an effect on the behavior of community members, while the intensity of social media use does not have a significant effect on the behavior of community members.